Variation in seed dormancy and Î±-amylase activity in Indian rice (Oryza sativa) accessions - RATHI, SUNAYANA; SARMA, RAMENDRA NATH; YADAV, RAJ NARAIN SINGH (The Indian Journal of Agricultural Sciences, 2013)
Lack of adequate seed dormancy is the major reason for pre-harvest sprouting in field under wet weather conditions. This results in significant economic loss for grain industry around the world. Objective of this study was to evaluate rice seed dormancy and the use of Î±-amylase enzyme activity as an indicator of dormancy level. There was, significant variation for degree of dormancy among 100 accessions, procured from the Regional Agricultural Research Station (RARS), Titabar, India. Cheniahu with highest duration of dormancy (25 days) can be a potential donor for dormancy, which can be exploited for development of rice variety with desired period of dormancy to resist the problem of pre- and post-harvest sprouting. Rice seeds were germinated and Î±-amylase activity was measured 0, 3, 5, 7, 10 and 12 days of germination. Significant steady increases in Ã¡-amylase activity were observed from third day of germination but decreased after 10 days of germination. The Î±-amylase activity was low in dormant genotypes and high in non-dormant genotypes and proved to be an efficient marker of the seeds dormancy level.